2012
DOI: 10.1309/ajcpgsj4nhfqmx9w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clot-Based vs Chromogenic Factor Xa Procoagulant Phospholipid Activity Assays

Abstract: We compared 2 commercial plasma procoagulant phospholipid activity (PPA) assays, chromogenic, using bound annexin V to capture phosphatidylserine-containing microparticles, and clot-based. In both, anionic phospholipids accelerated activation of prothrombin by factor Xa. PPA levels were lower in the chromogenic vs the clot-based assay, with poor correlation between methods: normal samples, mean ± SD, 27 ± 17 vs 590 ± 414 nmol/L (n = 24; r(2) = 0.29) and patient samples, mean ± SD, 45 ± 44 vs 401 ± 330 nmol/L (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…The contribution of PS to procoagulant activity can be measured in clot-based or chromogenic assays that provide functional measurements of procoagulant phospholipids [178]. …”
Section: Quality Of Platelet Concentratesmentioning
confidence: 99%
“…The contribution of PS to procoagulant activity can be measured in clot-based or chromogenic assays that provide functional measurements of procoagulant phospholipids [178]. …”
Section: Quality Of Platelet Concentratesmentioning
confidence: 99%
“…For example, a recent study has reported that larger microparticles show higher levels of procoagulant phospholipid activity than smaller microparticles, probably due to their greater surface area [31]. The size of the microparticles may have an effect on their function.…”
Section: Definition Of Microparticlesmentioning
confidence: 99%
“…[4,5]. Therefore, detection and measurement of MPs have a potential application in the study of different pathologies, as well as a prognostic role and could serve as a tool in monitoring effectiveness of therapy in the setting of major diseases.…”
mentioning
confidence: 99%
“…Increased procoagulant phospholipid activity (PPA) of MPs is associated with many pathological states, including cancer, cardiovascular disease, infection and inflammatory diseases, as well as other clinical states associated with platelet activation. [4,5]. Therefore, detection and measurement of MPs have a potential application in the study of different pathologies, as well as a prognostic role and could serve as a tool in monitoring effectiveness of therapy in the setting of major diseases.…”
mentioning
confidence: 99%